2015
DOI: 10.1007/s13312-015-0715-x
|View full text |Cite
|
Sign up to set email alerts
|

Waist-to-height ratio as an indicator of high blood pressure in urban Indian school children

Abstract: Obesity indicators, especially waist-to-height ratio due to its ease of measurement, can be useful initial screening tools for risk of high blood pressure in urban Indian school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Overall, 3.4% of students in government schools and 21.9% in private schools are either overweight or obese ( Arora et al, 2012 ; Jagadesan et al, 2014 ). Our results corroborate and extend the findings from previous regional studies in India ( Patnaik et al, 2015 ; Mishra et al, 2015 ; Khadilkar et al, 2014 ; Gupta et al, 2012 ). However, our results differ from findings from the developed world where overweight and obesity have been shown to be higher among low SES groups ( Stamatakis et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, 3.4% of students in government schools and 21.9% in private schools are either overweight or obese ( Arora et al, 2012 ; Jagadesan et al, 2014 ). Our results corroborate and extend the findings from previous regional studies in India ( Patnaik et al, 2015 ; Mishra et al, 2015 ; Khadilkar et al, 2014 ; Gupta et al, 2012 ). However, our results differ from findings from the developed world where overweight and obesity have been shown to be higher among low SES groups ( Stamatakis et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted with school children aged 10–16 years in Odisha (India) reported the prevalence of overweight and obesity to be 27.8% ( Patnaik et al, 2015 ). Likewise, a second study conducted in Bangalore, India reported the prevalence of overweight and obesity among children aged 6–16 years to be 15.1% ( Mishra et al, 2015 ). A study conducted in Kolkata, India with school children, aged 10–19 years found the prevalence of hypertension (systolic and/or diastolic blood pressure ≥ 95th percentile for gender, age and height) to be 10.1% ( Maiti and Bandyopadhyay, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have reported different findings. A study conducted in Indian schoolchildren aged 6–16 years showed that the AUC value of WHtR for high SBP was slightly higher than that of WC and BMI, while the AUC value of BMI for high DBP was slightly higher than that of WHtR and WC 47 . In a study conducted in Switzerland, Chiolero et al .…”
Section: Discussionmentioning
confidence: 96%
“…11 A study from urban Bangalore, among the 6-16 years old children the prevalence of hypertension was 10.7% (high SBP 8.0% and high DBP 2.7%). 12 A nationwide study in Pakistan involving children 5-14 years, the overall prevalence of hypertension was reported as 12.2% with higher prevalence among boys (15.8%) than girls (8.7%). 13 Among Brazilian school children aged 6-11 years, the prevalence of hypertension was 11.2% in normal-weight, 20.6% in overweight and 39.7% in obese children.…”
Section: Discussionmentioning
confidence: 99%